2014
DOI: 10.1007/s10661-014-3772-z
|View full text |Cite
|
Sign up to set email alerts
|

Natural attenuation of coal combustion waste in river sediments

Abstract: The weathering of coal combustion products (CCPs) in a lotic environment was assessed following the Tennessee Valley Authority (Kingston, TN) fly ash release of 2008 into surrounding rivers. Sampled materials included stockpiled ash and sediment collected from 180 to 880 days following the release. Total recoverable concentrations of heavy metals and metalloids in sediment were measured, and percent ash was estimated visually or quantified by particle counts. Arsenic and selenium in sediment were positively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Multiple leaching methods are in use and vary in specific steps but commonly are initiated with water extraction, then continue with more aggressive extractants (e.g., high molarities of nitric acid, ammonium acetate) and conclude with solvents and/or acids and perhaps heat (e.g., hydroxylamine hydrochloride in 25% acetic acid at 95°C for 15 h.) to extract metals and metalloids from mineral matrices (EPRI, 2006(EPRI, , 2008a(EPRI, , 2008bMarkwiese et al, 2014). Other works have shown that As leaching from and adsorption to ash particles are pH dependent; at pH b 3 or N7 increasing amounts of As are leached or desorbed from ash particles EPRI, 2010).…”
Section: Characteristics Of Arsenic Species Related To Coal Combustionmentioning
confidence: 99%
“…Multiple leaching methods are in use and vary in specific steps but commonly are initiated with water extraction, then continue with more aggressive extractants (e.g., high molarities of nitric acid, ammonium acetate) and conclude with solvents and/or acids and perhaps heat (e.g., hydroxylamine hydrochloride in 25% acetic acid at 95°C for 15 h.) to extract metals and metalloids from mineral matrices (EPRI, 2006(EPRI, , 2008a(EPRI, , 2008bMarkwiese et al, 2014). Other works have shown that As leaching from and adsorption to ash particles are pH dependent; at pH b 3 or N7 increasing amounts of As are leached or desorbed from ash particles EPRI, 2010).…”
Section: Characteristics Of Arsenic Species Related To Coal Combustionmentioning
confidence: 99%
“…The distribution of these elements in signi cant amounts into the different segments of nature may cause environmental pollution and health hazards (Rowe et al, 2002;Saha and Roychoudhury, 2019). Therefore, examination of these PHEs in feed coal is important for the consumption in thermal power plants from environmental aspects (Markwiese et al, 2014). Because the range of concentration of the PHEs in the coal samples is at a considerable level, a regular chemical analysis is urgently required for the burning of this fossil fuel in the thermal power plants because vulnerable exposure of the elements due to combustion may cause adverse effects on the environment (Finkelman, 2004;Saha and Roychoudhury, 2019).…”
Section: Loi Loss Of Ignitionmentioning
confidence: 99%
“…Deposition and leaching of the emitted particulate matter of toxic elements in the different environmental segments such as ground and surface water, soil, and sediment causes bioaccumulation and biomagni cations in the ecological pyramid (Bhattacharyya et al 2009;Markwiese et al, 2014). This leads adverse effect into the food-chain and nally human health (Finkelman, 2004;Markwiese et al, 2014). A lab-scale bio-availability test is performed to measure the potential mobility of hazardous elements into the living system.…”
Section: Laboratory Experiments For Evaluation Of Environmental Impac...mentioning
confidence: 99%
See 2 more Smart Citations